Electrospinning synthesis and negative thermal expansion of one-dimensional Sc2Mo3O12 nanofibers. Issue 7 (1st April 2023) - Liu, Hongfei; Huang, Feiyu; Wang, Wei; Meng, Xiangdong; Zhang, Zhiping
Abstract: Orthorhombic Sc2 (MoO4 )3 nanofibers have been prepared by ethylene glycol assisted electrospinning method. The effects of annealing temperature, precursor concentration, spinning distance and solvent on the preparation of Sc2 (MoO4 )3 nanofibers were characterized by XRD, SEM, HRTEM, EDX and high-temperature XRD. XRD analysis shows as-prepared nanofibers are amorphous. Orthorhombic Sc2 (MoO4 )3 nanofibers can be fabricated after annealing at different temperatures in 500–800 °C for 2 h. The crystallinity of Sc2 (MoO4 )3 nanofibers improves and the nanofiber diameter decreases gradually as the annealing temperature increases. However, the nanofiber structure was destroyed at the annealing temperature above 700 °C. Higher precursor concentration results in a slight increase of diameter and decrease in destroying temperature of Sc2 (MoO4 )3 nanofibers. Spinning distance also affects the diameter of nanofibers, and the nanofiber diameter decreases as the distance increases. One-dimensional orthorhombic Sc2 (MoO4 )3 nanofibers exhibit anisotropic negative thermal expansion. In 25–700 °C, the coefficients of thermal expansion (CTE) of α a, α b and α c are −5.81 × 10 −6 °C −1, 4.80 × 10 −6 °C −1 and -4.33 × 10 −6 °C −1, and the α l of Sc2 (MoO4 )3 nanofibers is −1.83 × 10 −6 °C −1 .